Cathode compositions for lithium-sulfur batteries containing blend of intercalated materials
By using a blended cathode between electroactive sulfur materials and non-sulfur active materials in lithium sulfur batteries, the problem of limited performance and efficiency of sulfur cathode is solved, and higher energy density and longer cycle life are achieved, reducing the cost of Cobalt and nickel dependence.
Patent Information
- Application Number
- CN202380042897.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-15
- Filing Date
- 2023-04-14
- Publication Date
- 2025-01-07
AI Technical Summary
Existing lithium-ion batteries face challenges of high energy density, long cycle life and low cost in commercial applications, especially when using sulfur cathodes, which have limited performance and efficiency due to sulfur complexity and by-products, and for cobalt and The dependence of nickel has environmental protection and supply problems.
Using blended cathode materials containing electroactive sulfur materials and non-sulfur active materials, the rate and efficiency characteristics of the sulfur cathode are improved by selecting suitable non-sulfur electroactive materials to match the discharge voltage curve of sulfur, for example, using metal chalcogenides, Transition metal oxides and polyanionic compounds form core-shell structures to optimize cell performance.
Improves the rate capability and state-of-charge dependency performance of lithium-sulfur batteries, extends battery life, reduces thermal management requirements, and reduces dependence on cobalt and nickel, achieving higher energy density and lower production costs.
Smart Images

Figure CN119278525A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of U.S. Provisional Patent Application No. 63 / 331,507, filed on April 15, 2022, the contents of which are hereby incorporated by reference in their entirety. Background Art
[0003] There is a lot of work going on to develop lithium-ion batteries with high energy density, long cycle life, and low cost, especially for use in electric vehicles and consumer electronics.
[0004] Sulfur is a low-cost, high-energy-density material that is available as a byproduct of the oil and gas industry. The use of sulfur in lithium battery cathodes has been under development for some time, but has yet to achieve widespread commercial application. Using sulfur can eliminate the need for cobalt and nickel in lithium batteries. Cobalt is expensive, toxic, and cobalt mining in some regions can be subject to loose regulation and unethical practices. Nickel has a high energy density, but there are concerns about its supply in the long term, such as the recent move that prompted Tesla to move away from nickel-containing batteries.
[0005] Producing sulfur cathodes that can achieve commercial performance levels has been a challenge, for example because sulfur byproducts can degrade performance and limit cycle life, and low density of single functional materials can negatively impact energy and power. There remains a need for lithium-ion batteries with improved energy density, longer cycle life, and lower cost.
[0006] The complexity of sulfur conversion chemistry poses additional challenges for sulfur cathodes. 8 ) to lithium sulfide (e.g., Li 2 The conversion of sulfur cathodes to S is a complex multi-step process involving many intermediate species with different chemical properties and solubilities. This complexity makes it difficult to achieve high discharge or charge rates for sulfur cathodes due to the kinetic limitations of the multi-step chemical conversions, and causes performance and efficiency to vary with the state of charge of the battery. These two features pose challenges for demanding applications such as the consumer automotive market. Summary of the invention
[0007] The present disclosure provides, inter alia, cathode materials and batteries including the cathode materials.The cathode material can include at least one electroactive sulfur material and two or more non-sulfur active materials (eg, a blend of two or more non-sulfur active materials).
[0008] In some aspects, the present disclosure relates to a cathode material comprising a mixture of a first active material and a second non-sulfur active material, wherein the first active material comprises at least one electroactive sulfur material, and the second non-sulfur active material comprises a blend of two or more non-sulfur electroactive materials (e.g., metal sulfide, transition metal oxide and / or polyanionic compound). The blend can be selected so that the discharge voltage curve of the blend has a voltage platform close to the discharge voltage curve of at least one electroactive sulfur material. In some embodiments, the cathode material is at least 10% by mass of non-sulfur electroactive material (e.g., metal sulfide) relative to sulfur, such as 10 to 90% by mass of non-sulfur electroactive material, such as 30 to 70% by mass of non-sulfur electroactive material.
[0009] In some embodiments, the voltage curves of the first active material and the second active material are measured separately under similar electrochemical conditions to evaluate whether they are close to each other.
[0010] In some embodiments, a blend of two or more non-sulfur electroactive materials has a discharge voltage profile characterized by the discharge voltage attributable to the blended non-sulfur material being within 10% (e.g., within 5%, within 3%, or within 1%) of the sulfur discharge voltage attributable to at least one electroactive sulfur material for at least 50% of the total discharge (e.g., for at least 60%, at least 75%, or at least 80% of the total discharge).
[0011] In some embodiments, the at least one electroactive sulfur material comprises at least one of the following (i) to (iv): (i) S 8 Sulfur in the form of a cyclic octaatomic molecule, (ii) lithium sulfide (e.g., Li 2 S 2 and / or Li 2 S), (iii) sulfur in the form of electroactive organosulfur compounds, and (iv) sulfur in the form of electroactive sulfur-containing polymers.
[0012] In some embodiments, each of the two or more non-sulfur electroactive materials (e.g., intercalation materials) has a separate discharge voltage curve whose voltage plateau is different from the voltage plateau of the separate discharge voltage curve of any other material in the two or more non-sulfur electroactive materials. In some embodiments, the blend of two or more non-sulfur electroactive materials comprises one or more chalcogenides (e.g., wherein each of the two or more non-sulfur electroactive materials is a chalcogenide) (e.g., comprises one or more metal chalcogenides, such as one or more metal sulfides). In some embodiments, each of the two or more non-sulfur electroactive materials (i) has a different crystal structure (e.g., layered, spinel, olivine, tavorite), (ii) has a different composition, or (iii) has both (i) and (ii).
[0013] In some embodiments, the second non-sulfur active material has a discharge voltage curve with two plateaus. In some embodiments, one of the two plateaus corresponds to a soluble / intermediate polysulfide conversion and the other of the two plateaus corresponds to a solid or quasi-solid product. In some embodiments, the discharge voltage curve of the second non-sulfur active material is close to sulfur to lithium sulfide (e.g., S 8 →Li 2 In some embodiments, the discharge voltage curve with two plateaus has a discharge voltage curve of about 2.2 to about 2.4 (V, relative to Li / Li + ) range and about 2.0 to about 2.2 (V, relative to Li / Li + ) within the scope of the second platform.
[0014] In some embodiments, at least one electroactive sulfur material has a discharge voltage curve with two plateaus. In some embodiments, one of the two plateaus corresponds to a soluble / intermediate polysulfide conversion and the other of the two plateaus corresponds to a solid or quasi-solid product. In some embodiments, the discharge voltage curve of the second non-sulfur active material is close to sulfur to lithium sulfide (e.g., S 8 →Li 2 In some embodiments, the discharge voltage curve with two plateaus has a discharge voltage curve of about 2.2 to about 2.4 (V, relative to Li / Li + ) range and about 2.0 to about 2.2 (V, relative to Li / Li + ) within the scope of the second platform.
[0015] In some aspects, the present disclosure relates to a cathode material comprising: an electroactive sulfur material and two or more non-sulfur electroactive materials (e.g., a blend of two or more non-sulfur electroactive materials). In some embodiments, the two or more electroactive materials together have a discharge voltage curve having at least two different voltage plateaus. The electroactive sulfur material may include at least one of the following (i) to (iv): (i) S 8 Sulfur in the form of a cyclic octaatomic molecule, (ii) lithium sulfide (e.g., Li 2 S 2 and / or Li 2 S), (iii) sulfur in the form of electroactive organic sulfur compounds, and (iv) sulfur in the form of electroactive sulfur-containing polymers. For example, the electroactive sulfur material may include (i) sulfur (S 8 ) and (ii) lithium sulfide (e.g., Li 2 S 2 and / or Li 2 The cathode material may include at least one of the non-sulfur electroactive materials (e.g., lithium intercalation materials).
[0016] In some embodiments, the two or more non-sulfur electroactive materials together have a discharge voltage curve that corresponds to the discharge voltage curve of sulfur (e.g., each of the two or more electroactive materials has a discharge voltage curve whose voltage plateau corresponds to the voltage plateau of the discharge voltage curve of sulfur). In some embodiments, each of the two or more non-sulfur electroactive materials has a separate discharge voltage curve whose voltage plateau is different from the voltage plateau of the separate discharge voltage curve of any other material of the two or more non-sulfur electroactive materials. In some embodiments, the voltage plateau of the separate discharge voltage curve of each of the two or more electroactive materials is within 10% (e.g., within 5%, within 3%, or within 1%) of the corresponding voltage plateau of the discharge voltage curve of sulfur.
[0017] In some embodiments, the cathode material comprises a core-shell structure. In some embodiments, the core-shell structure comprises a core each having a surrounding shell, the core comprising an electroactive sulfur material (e.g., S 8 , Li 2 S 2 and / or Li 2S), and the shell comprises at least one of two or more non-sulfur electroactive materials (e.g., one or more metal chalcogenides). In some embodiments, the core-shell structure has an average core diameter in the range of 50 to 300 nm and an average shell thickness in the range of 1 to 20 nm thick (e.g., no more than 10 nm thick). In some embodiments, the core-shell structure has at least 10% by mass of non-sulfur electroactive material (e.g., metal chalcogenide) relative to sulfur (e.g., 10 to 90% by mass of non-sulfur, non-carbon electroactive material, e.g., 30 to 70% by mass of non-sulfur, non-carbon electroactive material).
[0018] In some embodiments, the battery (e.g., a secondary battery) includes (i) a cathode comprising a cathode material disclosed herein (e.g., in the Summary of the Invention section) and (ii) an electrolyte (e.g., a solid state electrolyte (SSE)) in contact with the cathode. In some embodiments, the battery also includes an anode. In some embodiments, the anode is a protected lithium metal anode. In some embodiments, the battery also includes a protected current collector.
[0019] In some aspects, the present disclosure relates to a method of operating a lithium-sulfur battery. The lithium-sulfur battery may include a cathode comprising (i) sulfur or lithium sulfide (e.g., Li 2 S 2 and / or Li 2 S) (e.g., both sulfur and lithium sulfide), (ii) a first non-sulfur electroactive material (e.g., a first intercalation material), and (iii) a second non-sulfur electroactive material different from the first non-sulfur electroactive material (e.g., a second intercalation material). The method may include discharging the battery. Discharging the battery may include simultaneously inserting (e.g., intercalating) lithium into the first non-sulfur electroactive material while at least partially converting at least a portion of the sulfur or lithium sulfide (e.g., S) at a first voltage. 8 →Li 2 S). Discharging the battery can also include subsequently inserting (e.g., intercalating) lithium into a second non-sulfur electroactive material while at least partially (e.g., further) converting at least a portion of the sulfur (e.g., S) of the lithium sulfide at a second voltage different from the first voltage. 8 →Li 2 S). By completing both insertion steps simultaneously, the battery can be fully discharged.
[0020] In some embodiments, the method includes charging the battery after discharging the battery. Charging the battery can simultaneously include (i) removing lithium from the first non-sulfur electroactive material, (ii) removing lithium from the second non-sulfur electroactive material, and (iii) at least partially converting at least a portion of the sulfur or lithium sulfide (e.g., Li 2 O) at a third voltage (e.g., different from the first voltage and the second voltage).2 S→S 8 ).
[0021] In some aspects, the present disclosure relates to a method of operating a battery. The battery may include a cathode comprising (i) a sulfur electroactive material, (ii) a first non-sulfur electroactive material (e.g., a first intercalation material), and (iii) a second non-sulfur electroactive material different from the first non-sulfur electroactive material (e.g., a second intercalation material). The method may include discharging the battery. Discharging the battery may include simultaneously inserting (e.g., embedding) ions (e.g., lithium) into the first non-sulfur electroactive material while at least partially converting at least a portion of the sulfur electroactive material at a first voltage. Discharging the battery may also include subsequently simultaneously inserting (e.g., embedding) ions (e.g., lithium) into the second non-sulfur electroactive material while at least partially (e.g., further) converting at least a portion of the sulfur electroactive material [e.g., at least a portion of the lithium sulfide (e.g., S 8 →Li 2 S)]. By completing both insertion steps simultaneously, the battery can be fully discharged.
[0022] In some embodiments, the method includes charging the battery after discharging the battery. Charging the battery may include simultaneously (i) removing ions from the first non-sulfur electroactive material, (ii) removing ions from the second non-sulfur electroactive material, and (iii) at least partially converting at least a portion of the sulfur electroactive material [e.g., sulfur or lithium sulfide (e.g., Li 2 S→S 8 )].
[0023] In some aspects, the present disclosure relates to a cathode material comprising at least one electroactive sulfur material, for example comprising at least one of (i) sulfur (S8) and (ii) lithium sulfide (e.g., Li2S2 and / or Li2S), and two or more intercalation materials (e.g., lithium intercalation materials). In some embodiments, each of the two or more intercalation materials has a separate discharge voltage curve, and its voltage plateau is different from the voltage plateau of the separate discharge voltage curve of any other material in the two or more intercalation materials. In some embodiments, the blended discharge voltage curve is close to the discharge voltage curve of at least one electroactive sulfur material.
[0024] In some aspects, the present disclosure relates to a solid-state sulfur battery. The battery may include an anode; a solid electrolyte; and a cathode. The cathode may include a first active material, the first active material comprising at least one electroactive sulfur material. The cathode may also include one or more non-sulfur electroactive materials (e.g., metal chalcogenides, transition metal oxides, and / or polyanionic compounds). In some embodiments, the discharge voltage curve of the one or more non-sulfur electroactive materials is close to at least a portion of the discharge voltage curve of the at least one electroactive sulfur material [e.g., wherein the cathode material is at least 10% by mass of non-sulfur electroactive material (e.g., metal chalcogenide) relative to sulfur (e.g., 10 to 90% by mass of non-sulfur electroactive material, e.g., 30 to 70% by mass of non-sulfur electroactive material)].
[0025] In some embodiments, the one or more non-sulfur electroactive materials are a blend of two or more non-sulfur electroactive materials. In some embodiments, at least a portion of the discharge voltage curve includes two or more distinct portions, each portion corresponding to one of the two or more non-sulfur electroactive materials.
[0026] In some embodiments, the one or more non-sulfur electroactive materials comprise (eg, are) mixed metal sulfides.
[0027] In some embodiments, at least a portion of the discharge voltage curve exists in a voltage range of 2.5V to 1.9V (e.g., 2.3V to 2.1V) and / or a SoC range of 90% to 30% (e.g., 90% to 60%). In some embodiments, at least a portion of the discharge voltage curve is a sloped (e.g., gently and / or monotonically sloped) portion of the discharge voltage curve.
[0028] In some aspects, the present disclosure relates to a cathode material comprising a mixture of at least one electroactive sulfur material and at least one non-sulfur electroactive material, wherein the non-sulfur electroactive material is a mixed metal chalcogenide, wherein the discharge voltage curve of the at least one non-sulfur electroactive material corresponds to the discharge voltage curve of the at least one electroactive sulfur material.
[0029] In some embodiments, the at least one non-sulfur electroactive material comprises two non-sulfur electroactive materials (two mixed-metal chalcogenides). In some embodiments, the at least one non-sulfur electroactive material is a single non-sulfur electroactive material (single mixed-metal chalcogenide).
[0030] In some embodiments, the mixed-metal chalcogenide is a mixed-metal sulfide (eg, wherein the mixed-metal chalcogenide is a mixed-metal sulfide wherein the at least one non-sulfur electroactive material comprises two non-sulfur electroactive materials).
[0031] In some embodiments, the discharge voltage curve of at least one non-sulfur electroactive material has a voltage plateau that is close to the voltage plateau of at least one electroactive sulfur material. In some embodiments, at least one non-sulfur electroactive material has a discharge voltage curve characterized by the discharge voltage attributable to the at least one non-sulfur material being within 10% (e.g., within 5%, within 3%, or within 1%) of the sulfur discharge voltage attributable to the at least one electroactive sulfur material for at least 50% of the total discharge (e.g., for at least 60%, at least 75%, or at least 80% of the total discharge).
[0032] In some embodiments, the at least one electroactive sulfur material comprises at least one of the following (i) to (iv): (i) S 8 Sulfur in the form of a cyclic octaatomic molecule, (ii) lithium sulfide (e.g., Li 2 S 2 and / or Li 2 S), (iii) sulfur in the form of electroactive organosulfur compounds, and (iv) sulfur in the form of electroactive sulfur-containing polymers.
[0033] In some embodiments, the discharge voltage curve of at least one non-sulfur electroactive material has two voltage plateaus, wherein one of the two plateaus corresponds to soluble / intermediate polysulfide conversion and the other of the two plateaus corresponds to a solid or quasi-solid product. In some embodiments, the discharge voltage curve of at least one non-sulfur electroactive material has two voltage plateaus, wherein the first plateau is between about 2.2 and about 2.4 V relative to Li / Li. + ) range, and the second platform is about 2.0 to about 2.2 (V, relative to Li / Li + ) range. In some embodiments, at least one non-sulfur electroactive material has a discharge voltage curve close to sulfur to lithium sulfide (e.g., S 8 →Li 2 S) discharge voltage curve.
[0034] In some embodiments, the cathode material is at least 10 mass % non-sulfur electroactive material (e.g., mixed metal chalcogenide) relative to sulfur (e.g., 10 to 90 mass % non-sulfur electroactive material, e.g., 30 to 70 mass % non-sulfur electroactive material).
[0035] The battery can include (i) a cathode comprising a cathode material and (ii) an electrolyte (e.g., a solid state electrolyte (SSE)) in contact with the cathode. In some embodiments, the battery also includes an anode. In some embodiments, the anode is a protected lithium metal anode. In some embodiments, the battery also includes a protected current collector.
[0036] The cathode materials disclosed herein can be included in a cathode. The cathode can be located in an electrochemical cell. The electrochemical cell can be a battery. The battery can be a primary cell, a low cycle life battery, or a secondary battery. The battery can be, for example, a sulfur battery, such as a lithium sulfur battery.
[0037] Any two or more of the features described in this specification (including in this summary) may be combined to form an embodiment of the present disclosure, regardless of whether or not specifically and explicitly described as a separate combination in this specification. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] When with Figure 1 The teachings of the present invention described herein will be more fully understood from the following description of various exemplary embodiments when read together. It should be understood that the figures described below are for illustrative purposes only and are not intended to limit the scope of the teachings of the present invention in any way. The foregoing and other objects, aspects, features and advantages of the present disclosure will become more apparent and can be better understood by reference to the following description taken in conjunction with the accompanying drawings, in which:
[0039] Figure 1 is a schematic diagram illustrating an exemplary discharge curve for a lithium-sulfur battery operating with a liquid electrolyte;
[0040] Figure 2 is a diagrammatic representation of a cross-section of an electrochemical cell according to certain embodiments of the present disclosure; and
[0041] Figure 3 is a diagram of a cylindrical battery embodying the concepts of the present disclosure.
[0042] definition
[0043] About / approximately: When used herein to refer to a certain value, the term "about" or "approximately" refers to a value similar to the value referred to in the context. Generally speaking, those skilled in the art who are familiar with the context will understand the relevant degree of difference covered by "about" or "approximately" in the context. For example, in some embodiments, for example, as described herein, the term "about" can be included in a series of values within a portion of 25%, 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1% or one percent of the value referred to.
[0044] Intercalation Material: As used herein, the term "intercalation material" refers to a substance in which another substance or species (e.g., ions, metal ions) is reversibly inserted or contained in vacancies, interstitial sites, voids, between layers of the intercalation material, or some combination thereof.
[0045] Electroactive Material: As used herein, the term "electroactive material" refers to a composition of matter having one or more components that are capable of changing their oxidation state during the charge transfer step of an electrochemical reaction.
[0046] Lithium alloy: As used herein, the term lithium alloy refers to substances formed by the combination of lithium with other metallic or semi-metallic elements: non-limiting examples include lithium silicon compounds and alloys of lithium with metals such as sodium, cesium, indium, aluminum, zinc and silver.
[0047] Nanoparticles, nanostructures, nanomaterials: As used herein, these terms can be used interchangeably to refer to particles of nanoscale size or materials with nanoscale structures. Nanoparticles can have essentially any shape or configuration, such as tubes, wires, laminates, sheets, grids, boxes, cores and shells, or combinations thereof.
[0048] Substantially: As used herein, the term "substantially" refers to the qualitative condition of exhibiting the full or nearly full extent or degree of a characteristic or property of interest. DETAILED DESCRIPTION
[0049] One of the objectives of the present disclosure is to seek to improve the rate capability and state of charge (SoC) dependent performance characteristics that have so far limited the commercial application of lithium sulfur batteries. A cathode for a lithium sulfur battery is described herein, the cathode comprising a mixture of: i) an electroactive sulfur (e.g., S 8 ) and ii) a blended electroactive material comprising two or more non-sulfur electroactive materials, wherein the blended non-sulfur electroactive materials are selected such that the discharge voltage curve of the intercalation material blend (excluding the sulfur electroactive material) has a discharge voltage curve that substantially overlaps with the discharge voltage curve of the sulfur electroactive material. For example, in a typical ether electrolyte commonly used in sulfur batteries, S 8 →Li 2 The discharge voltage curve of S conversion has multiple plateaus (e.g., two plateaus), which is due to the multi-step conversion of sulfur into soluble / intermediate polysulfides (PS) and then progressing to solid or quasi-solid products (e.g., Li 2 S 2 / Li 2 S).
[0050] By matching the discharge curve with the provided non-sulfur electroactive material blend, one or more rate and efficiency characteristics of the sulfur cathode can be improved, such as during the entire battery discharge process. For example, while not wishing to be bound by any particular theory, the intercalation compound can provide a solid-state ion transport pathway into the electrode (e.g., cathode) by permeating through the intercalation material particles. In the case where the solid end product of sulfur charge / discharge blocks the pore structure of the electrode (e.g., cathode), the intercalation material can provide an alternative pathway for ion transport. In addition, the resistance of the electrolyte and the kinetics of sulfur electrochemical conversion vary with the charge state of the electrode (e.g., cathode). Such alternative pathways can allow the electrode (e.g., cathode) to reach equilibrium faster and / or achieve higher power, for example in an electrochemical cell (e.g., battery). The present disclosure provides electrodes comprising intercalation materials to provide voltage support under high-power pulses throughout the charge state of the device (e.g., battery), thereby improving the efficiency of the pulsed power (e.g., generating less heat and obtaining more usable energy from the pulse). The data show that an intercalation material included in an electrode (e.g., a cathode) comprising a sulfur electroactive material can change (e.g., improve) the rate capability of the electrode at different states of charge (e.g., high state of charge and low state of charge), such as without substantially changing the discharge voltage curve of the electrode compared to an otherwise equivalent electrode without the intercalation material. When a high power load on the cell is released, the intercalation material can then discharge into the sulfur material, and the intercalation material is regenerated for subsequent high load conditions. Lower heat generation has system-level advantages, in some embodiments, allowing for a reduction in thermal management infrastructure in a battery pack and requiring fewer cells to produce the same power.
[0051] Figure 1 is a schematic diagram illustrating a typical discharge curve for a lithium-sulfur battery operating with a liquid electrolyte. The discharge (lower red curve) shows two plateaus, the first being a plateau at about 2.37 V, which is believed to correspond to S 8 To soluble Li 2 S 8 , followed by a second plateau at about 2.1 V, which is believed to correspond to the reduction of polysulfides (PS) from higher order to lower order polysulfides (S 8 2- →S 6 2- →S 4 2- ), followed by Li as a solid or quasi-solid product 2 S 2 / Li 2 Deposition of S. Cell charging follows the inverse PS evolution, as illustrated by the upper blue curve.
[0052] Intercalation is the process of reversibly incorporating mobile ions or molecules into vacancies in the host network lattice. Intercalation minimizes volume changes and mechanical strains during repeated insertion and extraction of ions during charge and discharge. Intercalation cathodes contain a solid host network that can store guest ions that are reversibly inserted into and removed from the host network.
[0053] This article describes a technique for using a blend of intercalation active materials (e.g., non-sulfur intercalation materials) and / or non-sulfur conversion active materials, the blend being designed so that the discharge voltage curve of the blend follows the discharge curve of an electroactive sulfur material under similar conditions. In certain embodiments, a blend of two or more intercalation materials is mixed with an electroactive sulfur composition (e.g., S 8 Sulfur in the form of a cyclic octaatomic molecule, lithium sulfide (e.g., Li 2 S 2 and / or Li 2 The blend is selected so that the voltage plateau of its discharge voltage curve (regardless of the electroactive sulfur composition) is close to that of S 8 →Li 2 For example, a blend of intercalation materials in a liquid electrolyte has a discharge voltage curve characterized by the following: The voltages of the two plateaus are approximately Figure 1 The two plateaus of the discharge voltage curve shown are the same [e.g., the first plateau has a relative Li / Li + The potential is in the range of about 2.2 to about 2.4 V, and the second plateau (different from the first plateau) has a relative Li / Li +
[0043] Potentials in the range of about 2.0 to about 2.2 V, for example, when the same electrolyte is used for comparison, as electrolyte composition may affect the discharge voltage curve]. In certain embodiments, the distribution of the discharge capacity of the blended intercalation layer over its multiple discharge voltage plateaus approaches the capacity ratio observed on the discharge plateau of sulfur conversion.
[0054] One or more non-sulfur electroactive materials can be added to a battery (e.g., a lithium-sulfur battery) (e.g., at the cathode) to provide additional capacity to the battery. Additional capacity and / or rate capability can be added to a battery by providing a blend of electroactive materials that each have a discharge voltage curve that substantially overlaps the characteristics of the discharge curve of the electroactive sulfur in the battery to which the electroactive material is added (i.e., in the absence of the blended electroactive material). For example, the blended non-sulfur electroactive material can have a discharge voltage curve characterized by: for at least 50% of the total discharge (e.g., the total discharge of the battery) (e.g., at least 60%, at least 75%, or at least 80% of the total discharge (e.g., the total discharge of the battery)), the discharge voltage attributable to the blended material is within 10% (e.g., within 5%, within 3%, or within 1%) of the sulfur discharge voltage attributable to the sulfur electroactive material. Individual discharge voltage curves for non-sulfur electroactive materials can be obtained from the literature and / or can be obtained experimentally. The discharge voltage curve of a combination (eg, a blend) of two or more non-sulfur electroactive materials can be obtained experimentally or estimated (eg, by simulation).
[0055] Lithium-sulfur batteries operate by converting electroactive sulfur and lithium metal in a charged state into lithium sulfide in a discharged state. In certain lithium-sulfur battery systems, the process is characterized by two distinct voltage plateaus during discharge. In certain embodiments, the provided blended non-sulfur electroactive material may have a discharge voltage curve characterized by a voltage plateau that substantially overlaps a voltage plateau in the discharge voltage curve of the sulfur electroactive material to be combined with the blend. For example, referring to Figure 1 , one electroactive material in the non-sulfur blend may have a voltage plateau corresponding to a plateau of approximately 2.2-2.4 V, and another electroactive material in the blend may have a voltage plateau corresponding to a plateau of approximately 2.0-2.2 V (although the exact values may vary slightly for different electrochemical environments (e.g., electrolytes).
[0056] A region in a discharge curve of a provided cathode (e.g., in a battery) where the discharge voltage is relatively constant when the discharge current is held constant is a voltage plateau. The term "plateau" does not necessarily imply that the discharge potential does not change at all, but rather that the rate of change of the discharge voltage with change in state of charge (SoC) is small in a particular region relative to other portions of the cathode (e.g., battery) discharge curve. By way of example, Figure 1An exemplary discharge voltage curve for a typical lithium-sulfur cell discharged at a constant current is shown. Inspection of the discharge curve reveals at least four distinct regions: an initial region 102, where the cell has a relatively constant discharge voltage of about 2.35 volts; a second region 104, where the discharge voltage has a steeper slope that rapidly decreases from about 2.35 volts to 2.1 volts; followed by a third region 106, which also exhibits a relatively constant discharge voltage of about 2.1 volts; and then finally a region 108, which is also characterized by a steep decrease in discharge voltage near the end of discharge. In systems of this type, the term "plateau" has a common meaning and refers to regions such as 102 and 106 where the slope of voltage versus total discharge (or time in the case of constant current discharge) is low relative to adjacent regions of steeper slopes.
[0057] The discharge voltage curve of the battery may or may not have one or more voltage plateaus. For example, in some embodiments, the solid-state sulfur battery has a discharge voltage curve, at least a portion of which is monotonically inclined. The monotonically inclined portion may be relatively long and moderately inclined. Regardless of whether there is a voltage plateau in such a discharge voltage curve, one or more intercalation materials that are close to at least a portion of the discharge curve of the battery (such as a solid-state battery (e.g., a solid-state sulfur battery)) can be selected. In some embodiments, a blend of two or more non-sulfur electroactive materials (e.g., intercalation materials) may be included in the cathode material, wherein each of the materials is close to at least a portion (e.g., a different portion) of the discharge voltage curve. Such a portion of the discharge voltage curve may exist within a specific voltage range (e.g., 2.3V to 2.1V) and / or a specific SoC range (e.g., between 90% and 60% SoC).
[0058] In some embodiments, the discharge voltage curve of the non-sulfur electroactive material (e.g., intercalation material) corresponds to (e.g., is close to) the discharge voltage curve of at least one sulfur electroactive material. For example, in some embodiments, the discharge voltage of the non-sulfur electroactive material corresponds to the voltage plateau of the discharge voltage curve of at least one sulfur electroactive material, or the voltage plateau of the discharge voltage curve of the non-sulfur electroactive material corresponds to the voltage plateau of the discharge voltage curve of at least one sulfur electroactive material. As another example, in some embodiments, the discharge voltage curve of the non-sulfur electroactive material corresponds to (e.g., is close to) the discharge voltage curve of at least one sulfur electroactive material, wherein the discharge voltage of the non-sulfur electroactive material is (i) within 0.3V (e.g., within 0.2V, within 0.1V, or within 0.05V) and / or (ii) within 10% (e.g., within 5%, within 3%, or within 1%) of the discharge voltage of at least one sulfur electroactive material in at least a portion of the discharge voltage curve of the at least one sulfur electroactive material. For example, this may be the case in a solid-state sulfur battery or a liquid battery. At least a portion of the discharge voltage curve of at least one sulfur electroactive material may be defined by a voltage range and / or a SoC range. The voltage range can be, for example, 2.5V to 1.9V, 2.4V to 2.0V, 2.3V to 2.1V, 2.5V to 2.0V, 2.5V to 2.1V, 2.5V to 2.2V, 2.4V to 2.1V, 2.4V to 2.2V, 2.3V to 2.0V, 2.3V to 1.9V, 2.2V to 1.9V, or 2.2V to 2.0V. The SoC range can be, for example, 90% to 30% SoC, 90% to 40% SoC, 90% to 50% SoC, 90% to 60% SoC, 90% to 70% SoC, 80% to 30% SoC, 80% to 40% SoC, 80% to 50% SoC, 80% to 60% SoC, 70% to 30% SoC, 70% to 40% SoC, 70% to 50% SoC, 60% to 30% SoC, or 60% to 40% SoC. In some embodiments, the discharge voltage of the non-sulfur electroactive material or the portion of the discharge voltage curve of at least one sulfur electroactive material to which the discharge voltage curve corresponds (e.g., is close) is sloped. For example, it can be moderately sloped (e.g., in certain solid-state sulfur cells), monotonically sloped, or moderately monotonically sloped.
[0059] During operation of a lithium-sulfur battery comprising a blend of two or more non-sulfur electroactive materials provided, each electroactive material can store or release ions, and thus can be charged in addition to the ions / charge stored by the electroactive sulfur, respectively. In some embodiments, a method of operating a battery includes converting at least a portion of the electroactive sulfur during discharge while inserting (e.g., embedding) lithium ions into a first electroactive material at a first voltage. For example, lithium can be inserted into (e.g., embedded into) the first electroactive material by storing lithium on the surface of the electroactive material or in the bulk of the electroactive material (e.g., in vacancies, interstitial locations, in voids, or between layers of the electroactive material, or some combination thereof). The conversion of the electroactive sulfur in the steps can be along the S 8 To Li 2 S pathway occurs. (For at least a substantial portion (e.g., at least 80%) of the initial electroactive sulfur present at full charge, the conversion can be completely complete (at least converted to Li 2 S 2 and / or Li 2 This simultaneous conversion and insertion into the first electroactive material may occur at the first voltage plateau in the discharge voltage curve of the battery (e.g., about 2.2-2.4 V, reference Figure 1 ).
[0060] In some embodiments, the method of operating a battery further comprises converting at least a portion of the electroactive sulfur during discharge while inserting (e.g., intercalating) lithium into a second electroactive material at a second voltage different from the first voltage. For example, lithium can be inserted into (e.g., intercalated into) the second electroactive material by storing lithium on the surface of the electroactive material or in the bulk of the electroactive material (e.g., in vacancies, interstitial locations, voids, or between layers of the electroactive material, or some combination thereof). The second voltage can be lower than the first voltage. The conversion of sulfur or lithium sulfide in the steps can be along the S 8 To Li 2 The pathway of S occurs, for example, later in the conversion pathway than the first step using the first electroactive material. This simultaneous conversion and insertion into the second electroactive material may occur at a second voltage plateau in the discharge voltage curve of the battery (e.g., about 2.0-2.2 V, reference Figure 1 The second step using the second electroactive material can occur sequentially with (e.g., after) the first step using the first electroactive material (e.g., if Figure 1 This occurs when two electroactive materials are added during charging of the cell shown, one for each voltage plateau).
[0061] In some embodiments, a battery incorporating multiple electroactive materials as described above can be charged by simultaneously performing the following operations at a third voltage: (i) removing (e.g., deintercalating) lithium from a first electroactive material, (ii) removing lithium from a second electroactive material, and (iii) converting at least a portion of the lithium sulfide (or lithium polysulfide) to a more oxidized sulfur species (e.g., longer chain polysulfides or elemental sulfur). The conversion of at least a portion of the lithium polysulfide or lithium sulfide can be along the Li 2 S to S 8 (For at least a substantial portion (e.g., at least 80%) of the initial lithium sulfide present upon full discharge, the conversion can be fully completed when the battery is fully charged (e.g., converted to S 8 ).) The third voltage can be different from the first voltage and / or the second voltage (eg, higher than one or both).
[0062] In certain embodiments described herein, the discharge voltage curve of the blended electroactive material (e.g., intercalation material) is compared to the discharge voltage curve of sulfur. For example, the discharge voltage curve of the electroactive material (e.g., intercalation material) is described as corresponding to or close to the discharge voltage curve of sulfur. Such comparisons can be made by independently measuring the discharge voltage curves of the electroactive sulfur and the blended non-sulfur electroactive material in an otherwise similar or identical electrochemical environment. For example, when considering the same electrochemical environment (e.g., the same electrolyte and / or anode) (the difference is that the sulfur is replaced by the electroactive material (or added to the sulfur)), the discharge voltage curve of the electroactive material may have a voltage platform close to the voltage platform of the discharge voltage curve of sulfur.
[0063] In certain embodiments, in a solution containing electroactive sulfur (e.g., S 8 Sulfur in the form of a cyclic octaatomic molecule) and / or lithium sulfide (e.g., Li 2 S 2 and / or Li 2 S) using a blend of two or more intercalation materials in the cathode. In certain embodiments, the blend of intercalation materials comprises two or more intercalation materials, each material having a discharge voltage plateau different from each other, so that the blend has a discharge voltage curve containing two or more plateaus.
[0064] In certain embodiments, the blend of two or more intercalation materials comprises one or more chalcogenides (e.g., wherein at least one of the two or more intercalation materials is a chalcogenide). In certain embodiments, the chalcogenide has at least one chalcogen anion (oxygen, sulfur, selenium, tellurium, or polonium anion) and at least one electropositive element. In certain embodiments, the one or more chalcogenides may be based on sulfides, selenides, or tellurides. In certain embodiments, the one or more chalcogenides include metal sulfides. In certain embodiments, the one or more chalcogenides include one or more of the following: TiS 2 、LiTiS 2 (LTS), VS 2 、MoS 2 、Mo 2 S 8 、TaS 2 and NbSe 3 In certain embodiments, the one or more chalcogenides include transition metal oxides and / or polyanionic compounds. In certain embodiments, the one or more chalcogenides include metal monochalcogenides having the formula MX, wherein M is a transition metal and X is S, Se, or Te. In certain embodiments, the one or more chalcogenides include at least one of the formula MX 2 A transition metal dichalcogenide (TMD) wherein M is a transition metal (e.g., Ti, V, Co, Ni, Zr, Nb, Mo, Tc, Rh, Pd, Hf, Ta, W, Re, Ir, or Pt), and wherein X is S, Se, or Te. In certain embodiments, the one or more chalcogenides include materials having a layered crystal structure (e.g., LiTiS 2 、LiCoO 2 、LiNiO 2 、LiMnO 2 、LiNi 0.33 Mn 0.33 Co 0.33 O 2 、LiNi 0.8 Co 0.15 Al 0.05 O 2 or Li 2 MnO 3 ), materials having a spinel crystal structure (e.g., LiMn 2 O 4 or LiCo 2 O 4 ), materials with an olivine crystal structure (e.g., LiFePO 4 、LiMnPO 4 or LiCoPO 4) and / or a material having a ferroxene crystal structure (e.g., LiFeSO 4 F or LiVPO 4 F).
[0065] In certain embodiments, one or more non-sulfur electroactive materials include a mixed metal sulfide (MMS) (e.g., rather than a physical blend of two or more pure metal sulfides). Such mixed metal sulfides contain two or more transition metals in their crystal lattice. The MMS can have a discharge voltage curve with one or more voltage plateaus (e.g., each voltage plateau is attributed to one of its constituent metals). The discharge voltage curve of the MMS can correspond to (e.g., be close to) the discharge voltage curve of at least one sulfur electroactive material. In certain embodiments, the non-sulfur electroactive material is a material of the formula Ti x M y S z MMS, wherein M is a transition metal other than titanium, and x, y, and z are any values that allow the MMS to have a chemically stable structure. In certain embodiments, the non-sulfur electroactive material is of the formula Mo x M y S z MMS, wherein M is a transition metal other than molybdenum, and x, y, and z are any values that allow the MMS to have a chemically stable structure. In certain embodiments, the non-sulfur electroactive material is of formula V x M y S z MMS, wherein M is a transition metal other than vanadium, and x, y, and z are any values that allow the MMS to have a chemically stable structure. In certain embodiments, the non-sulfur electroactive material is of the formula Fe x M y S z wherein M is a transition metal other than iron, and x, y, and z are any values that allow the MMS to have a chemically stable structure. In certain embodiments, the non-sulfur electroactive material is a material of the formula Ta x M y S z MMS wherein M is a transition metal other than tantalum, and x, y, and z are any values that allow the MMS to have a chemically stable structure. In certain embodiments, any of the foregoing MMS formulas is characterized in that 2(x+y)=z.
[0066] In certain embodiments, the non-sulfur electroactive material is a MMS containing three transition metals. In certain embodiments, the MMS has the formula Ti x M y M' Y’ S z, wherein M and M' are each a metal other than titanium, and x, y, y' and z are any values that allow the MMS to have a chemically stable structure. In certain embodiments, the MMS has the formula Mo x M y M' Y’ S z , wherein M and M' are each a metal other than platinum, and x, y, y' and z are any values that allow the MMS to have a chemically stable structure. In certain embodiments, the MMS has the formula V x M y M' Y’ S z , wherein M and M' are each a metal other than vanadium, and x, y, y' and z are any values that allow the MMS to have a chemically stable structure. In certain embodiments, the MMS has the formula Fe x M y M' Y’ S z , wherein M and M' are each a metal other than iron, and x, y, y' and z are any values that allow the MMS to have a chemically stable structure. In certain embodiments, any of the foregoing MMS formulas is characterized in that 2(x+y+y')=z.
[0067] In certain embodiments, the non-sulfur electroactive material comprises a chemically stable MMS having the following stoichiometric formula: Mo x Ti y S z (For example, Mo 0.5 Ti 0.5 S 2 )、Ni x Co y S z (For example, Ni x Co 3-x S 4 、Co x Ni 1-x S 2 、Ni 3.5 Co 3.5 S 8 、Ni 3 Co 6 S 8 ),Cu x Co y S z (For example, CuCo 2 S 4 )、Zn x Co y S z (For example, Zn x Co 1-x S), Mnx Co y S z (For example, MnCo 2 S 4 ), Fe x Co y S z (For example, Fe x Co 1-x S 2 )、Ni x Fe y S z (For example, Ni x Fe 1-x S 2 、FeNiS 2 、Ni x Fe 3-x S 4 (For example, Ni 2 FeS 4 ))、Ni x Mo y S z (For example, Ni x Mo 4-x S 4 (For example, NiMo 3 S 4 )、M x Mo 6 S 8-y (For example, Cu x Mo 6 S 8-y 、Ag x Mo 6 S 8-y , Fe x Mo 6 S 8-y Cr x Mo 6 S 8-y 、Co x Mo 6 S 8-y 、Ni x Mo 6 S 8-y , Cu 2 MoS 4 )、M x Sb y S z (wherein M=Cu, Co or Bi) or M x Sn y S z(where M = Cu or Co). Examples of such and other materials that can be used as non-sulfur electroactive materials in cathode materials (e.g., in the cathode) are discussed in Yu, XY and Lou, XW, Mixed Metal Sulfides for Electrochemical Energy Storage and Conversion, Adv. Energy Mater. 8: 17015921 (2018); doi: 10.1002 / aenm.201701592.
[0068] In some embodiments, mixed metal chalcogenides (MMCs) are used as non-sulfur electroactive materials. The chalcogen in the MMC can be oxygen, sulfur (i.e., the MMC is an MMS), selenium, or tellurium. In some embodiments, the chalcogen in the MMC is not sulfur. Each MMS example in the preceding paragraph contemplates a corresponding MMC that does not use sulfur as the chalcogen.
[0069] Furthermore, it was found that the use of such blends of two or more intercalation materials (e.g., comprising one or more chalcogenides) resulted in improvements in PS behavior, leading to better battery performance, such as extended battery life, improved volumetric and coulombic efficiencies, and improved cycling performance, while ignoring or reducing capacity fade. Attempts have been made to control PS behavior (e.g., dissolution, diffusion, shuttling, and anode corrosion) in lithium-sulfur batteries via cathode and electrolyte formulation and design. These include techniques that attempt to inhibit detrimental PS formation and / or dissolution (PS-bypass), as well as techniques that attempt to favorably retain PS in the Li-S system (PS-retain). Without wishing to be bound by any particular theory, it is assumed that the use of a battery having a structure similar to that of S as described herein may result in improved PS performance. 8 →Li 2 Intercalation material blends (e.g., including one or more sulfides) that improve the discharge voltage profile of S enable a balance between PS bypassing and PS retention strategies in cathode formulations and designs that are not achievable with other technologies. For example, the use of intercalation material blends can suppress PS shuttling effects, thereby minimizing their deleterious effects on battery operation. In addition, the use of intercalation material blends described herein can reduce the undesirable generation and / or dissolution of long-chain PS anions. In addition, the use of intercalation material blends described herein in sulfur and / or lithium sulfide cathodes can allow for higher sulfur loadings and lower electrolyte to sulfur (E / S) ratios compared to other PS management technologies, thereby helping to improve the energy density of lithium-sulfur batteries.
[0070] In some embodiments, the lithium-sulfur battery of the present disclosure includes a lithium anode, a sulfur-based cathode [e.g., comprising a sulfur electroactive material and two or more non-sulfur electroactive materials (e.g., a blend of two or more non-sulfur electroactive materials)] and an electrolyte that allows ions to be transported between the anode and the cathode. In certain embodiments described herein, the anode portion of the battery comprises an anode and a portion of the electrolyte in contact therewith. Similarly, in certain embodiments described herein, the cathode portion of the battery comprises a cathode and a portion of the electrolyte in contact therewith. In certain embodiments, the battery includes a lithium ion permeable separator that defines a boundary between the anode portion and the cathode portion. In certain embodiments, the battery includes a housing that surrounds the anode portion and the cathode portion. In certain embodiments, the battery housing includes a conductive anode end cap electrically connected to the anode and a conductive cathode end cap electrically connected to the cathode to facilitate charging and discharging via an external circuit.
[0071] cathode
[0072] The compositions disclosed herein can be used to manufacture electrochemical devices. They may be porous or non-porous. Certain compositions disclosed herein will adhere to a current collector to form a cathode of a secondary sulfur battery. The cathode composition provided may include one or more additives, such as conductive particles, adhesives, and other functional additives commonly found in battery cathode mixtures. Generally speaking, the composition provided includes abundant conductive particles to increase the conductivity of the cathode and provide a low resistance path for electrons to enter the cathode so manufactured. In various embodiments, other additives are included in the composition to change or otherwise enhance the cathode produced according to the principles described herein. Other cathode components include, for example, current collectors, connectors, etc.
[0073] As discussed above, in certain embodiments, the cathode composition comprises sulfur (e.g., S 8 Sulfur in the form of a cyclic octaatomic molecule) and / or lithium sulfide (e.g., Li 2 S 2 and / or Li 2 S). In certain embodiments, the blend of intercalation materials comprises two or more intercalation materials, each of which has a discharge voltage platform different from each other, so that the blend has a discharge voltage curve containing two or more platforms. In certain embodiments, the blend of two or more intercalation materials is selected so that the voltage platform of its discharge voltage curve (excluding sulfur and / or lithium sulfide) is close to S 8 →Li 2 The voltage platform of the discharge voltage curve of S.
[0074] In certain embodiments, the blend of two or more intercalation materials comprises one or more chalcogenides (e.g., wherein each of the two or more intercalation materials is a chalcogenide). In certain embodiments, the chalcogenide has at least one chalcogen anion (oxygen, sulfur, selenium, tellurium, or polonium anion) and at least one electropositive element. In certain embodiments, the one or more chalcogenides may be based on sulfides, selenides, or tellurides. In certain embodiments, the one or more chalcogenides include metal sulfides. In certain embodiments, the one or more chalcogenides include one or more of the following: TiS 2 、TiS 3 、LiTiS 2 (LTS) and NbSe 3 In certain embodiments, the one or more chalcogenides include transition metal oxides and / or polyanionic compounds. In certain embodiments, the one or more chalcogenides include metal monochalcogenides having the formula MX, wherein M is a transition metal and X is S, Se, or Te. In certain embodiments, the one or more chalcogenides include at least one of the formula MX 2 A transition metal dichalcogenide (TMD) wherein M is a transition metal (e.g., Ti, V, Co, Ni, Zr, Nb, Mo, Tc, Rh, Pd, Hf, Ta, W, Re, Ir, or Pt), and wherein X is S, Se, or Te. In certain embodiments, the one or more chalcogenides include materials having a layered crystal structure (e.g., LiTiS 2 、LiCoO 2 、LiNiO 2 、LiMnO 2 、LiNi 0.33 Mn 0.33 Co 0.33 O 2 、LiNi 0.8 Co 0.15 Al 0.05 O 2 or Li 2 MnO 3 ), materials having a spinel crystal structure (e.g., LiMn 2 O 4 or LiCo 2 O 4 ), materials with an olivine crystal structure (e.g., LiFePO 4 、LiMnPO 4 or LiCoPO 4 ) and / or a material having a ferroxene crystal structure (e.g., LiFeSO 4 F or LiVPO 4 F).
[0075] In some embodiments, the non-sulfur electroactive material comprises particles (e.g., nanoparticles). For example, sulfide particles can be used as non-sulfur electroactive materials. A blend of two or more non-sulfur electroactive materials can comprise a blend of two types of particles (e.g., two different sulfides), particles comprising a blend of two non-sulfur electroactive materials (e.g., particles comprising two different sulfides), or both. In some embodiments, particles of non-sulfur electroactive materials are distributed (e.g., dispersed) throughout the cathode material. The cathode material can comprise particles comprising a sulfur electroactive material (e.g., particles of a sulfur electroactive material). One or more non-sulfur electroactive materials can form one or more discrete and / or one or more interconnected (e.g., charge and / or ion) transport pathways through the cathode material (e.g., in the cathode of a battery). One or more non-sulfur electroactive materials can be distributed (e.g., dispersed) throughout the sulfur electroactive material matrix (e.g., comprising one or more than one sulfur electroactive material). As described elsewhere, at least one non-sulfur electroactive material in the blend can be contained in the shell of a core-shell particle, the core-shell particle comprising a core of a sulfur electroactive material. Particle (for example, nanoparticle) can have any suitable shape, such as for example rod-like, flaky, tubular, spherical. Particle can be porous or non-porous. Particle can have any suitable size. In some embodiments, the size of particle is not more than 500 microns, not more than 250 microns, not more than 100 microns, not more than 50 microns, not more than 20 microns, not more than 10 microns, not more than 5 microns, not more than 1 micron, not more than 500 nanometers, not more than 400 nanometers, not more than 300 nanometers, not more than 250 nanometers, not more than 200 nanometers, not more than 100 nanometers or not more than 50 nanometers.
[0076] In certain embodiments, the cathode composition contains a conductive material and a binder. In certain embodiments, the conductive material includes a conductive material that is conducive to the movement of electrons in the composite material. For example, in certain embodiments, the conductive material is selected from the group consisting of: carbon-based materials, graphite-based materials, conductive polymers, metals, semiconductors, metal oxides, metal sulfides and combinations thereof. In certain embodiments, the conductive material includes a carbon-based material. For example, in certain embodiments, the provided cathode composition can include 3D structured graphene (for example, as described in U.S. Patent No. 11,299,397 (LytEn, Inc.), the text of which is incorporated herein by reference in its entirety). In certain embodiments, the conductive material includes a graphite-based material. In certain embodiments, the cathode composition does not contain carbon or contains a small amount of carbon (for example, not more than 5.0 weight %, not more than 3.0 weight %, not more than 2.0 weight %, not more than 1.0 weight %, or not more than 0.5 weight %).
[0077] In certain embodiments, the conductive material is selected from the group consisting of conductive carbon powders such as carbon black, Super C-NERGY TM Super C65, black, Acetylene black, synthetic graphite, such as SFG-6, SFG-15, SFG-44, KS-6, KS-15, KS-44, natural flake graphite, carbon nanotubes, fullerenes, hard carbon, intermediate carbon microspheres, etc. In certain embodiments, the conductive material includes one or more conductive polymers. For example, in certain embodiments, the conductive polymer is selected from the group consisting of: polyaniline, polythiophene, polyacetylene, polypyrrole, etc. In some embodiments, the conductive polymer is a cationic polymer. In some embodiments, the cationic polymer is a quaternary ammonium polymer. In certain embodiments, the cationic polymer is selected from the group consisting of: polydiallyldimethylammonium salt, poly[(3-chloro-2-hydroxypropyl)methacryloyloxyethyldimethylammonium salt, poly(butyl acrylate-methacryloyloxyethyltrimethylammonium) salt, poly(1-methyl-4-vinylpyridinium) salt, poly(1-methyl-2-vinylpyridinium) salt and poly(methacryloyloxyethyltriethylammonium) salt. In certain embodiments, the cationic polymer is selected from polydiallyldimethylammonium chloride (polyDADMAC), polybrene, epichlorohydrin-dimethylamine (epi-DMA), poly[(3-chloro-2-hydroxypropyl)methacryloyloxyethyldimethylammonium chloride], poly(acrylamide-methacryloyloxyethyltrimethylammonium bromide), poly(butyl acrylate-methacryloyloxyethyltrimethylammonium bromide), poly(1-methyl-4-vinylpyridinium bromide), poly(1-methyl-2-vinylpyridinium bromide), and poly(methacryloyloxyethyltriethylammonium bromide). In certain embodiments, the conductive material comprises one or more metal oxides or sulfides. For example, in certain embodiments, the conductive material comprises one or more oxides or sulfides of a first row transition metal such as titanium, vanadium, chromium, manganese, iron, cobalt, copper, zinc, or a combination thereof. For example, in certain embodiments, the conductive material comprises one or more oxides or sulfides of a second row transition metal such as zirconium, indium, tin, antimony, or a combination thereof. In certain embodiments, the conductive material is used alone. In other embodiments, the conductive material is used as a mixture of two or more conductive materials described above.
[0078] In certain embodiments, the provided cathode composition materials include a binder. The binder is typically a polymeric material that helps to adhere the individual particles that make up the cathode mixture into a stable composite material. Representative binders include polyvinylidene fluoride, poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF / HFP), polytetrafluoroethylene (PTFE), Kynar 2801, Powerflex LBG, HSV 900, Carboxymethyl cellulose, styrene butadiene rubber (SBR), polyethylene oxide, polypropylene oxide, polyethylene, polypropylene, polyacrylate, polyvinyl pyrrolidone, polymethyl methacrylate, polyethyl acrylate, polytetrafluoroethylene, polyvinyl chloride, polyacrylonitrile, polycaprolactam, polyethylene terephthalate, polybutadiene, polyisoprene or polyacrylic acid, or derivatives, mixtures or copolymers of any of these materials. In some embodiments, adhesive is a water-soluble adhesive, such as sodium alginate, carrageenan or carboxymethyl cellulose. Generally speaking, adhesive keeps active material together and contacts with current collector (for example, metal foil, such as aluminum, stainless steel or copper or conductive carbon sheet). In certain embodiments, the adhesive is selected from the group consisting of: polyvinyl acetate, polyvinyl alcohol, polyethylene oxide, polyvinyl pyrrolidone, alkylated polyethylene oxide, crosslinked polyethylene oxide, polyvinyl ether, polymethyl methacrylate, polyvinylidene fluoride, copolymer of polyhexafluoropropylene and polyvinylidene fluoride, polyethyl acrylate, polytetrafluoroethylene, polyvinyl chloride, polyacrylonitrile, polyvinyl pyridine, polystyrene and derivatives thereof, mixtures and copolymers. In some embodiments, the adhesive is a cationic polymer. In some embodiments, the adhesive is a quaternary ammonium polymer. In some embodiments, the adhesive is a cationic polymer as described above.
[0079] In certain embodiments, cathode also includes coating.For example, in certain embodiments, coating includes polymer, organic material, inorganic material or its mixture, and it is not an integral part of porous composite material or current collector.In certain such embodiments, polymer is selected from the group consisting of: copolymer of polyvinylidene fluoride, polyvinylidene fluoride and hexafluoropropylene, poly (vinyl acetate), poly (vinyl alcohol butyral-to-vinyl alcohol-to-vinyl acetate), poly (methyl methacrylate-to-ethyl acrylate), polyacrylonitrile, polyvinyl chloride-to-vinyl acetate, polyvinyl alcohol, poly (1-vinyl pyrrolidone-to-vinyl acetate), cellulose acetate, polyvinyl pyrrolidone, polyacrylate, polymethacrylate, polyolefin, polyurethane, polyvinyl ether, acrylonitrile-butadiene rubber, styrene butadiene rubber, acrylonitrile-butadiene styrene, sulfonated styrene / ethylene-butylene / styrene triblock copolymer, polyethylene oxide and its derivatives, mixture and copolymer.In some embodiments, coating includes cationic polymer.In some embodiments, coating includes quaternary ammonium polymer.In some embodiments, coating includes cationic polymer as described above. In certain such embodiments, the inorganic material includes, for example, colloidal silica, amorphous silica, surface-treated silica, colloidal alumina, amorphous alumina, tin oxide, titanium oxide, titanium sulfide (TiS 2 ), vanadium oxide, zirconium oxide (ZrO 2 ), iron oxide, iron sulfide (FeS), iron titanate (FeTiO 3 ), barium titanate (BaTiO 3 ) and combinations thereof. In certain embodiments, the organic material comprises conductive carbon.
[0080] Materials suitable for cathode mixtures are disclosed in Cathode Materials for Lithium Sulfur Batteries: Design, Synthesis, and Electrochemical Performance, Lianfeng et al., Interchopen.com, published on June 1, 2016, and The strategies of advanced cathode composites for lithium-sulfur batteries, Zhou et al., SCIENCE CHINA Technological Sciences, Vol. 60, No. 2: 175-185 (2017), the complete disclosures of each of which are hereby incorporated by reference into this document.
[0081] In certain embodiments, the cathode includes one or more of the following features: (a) a "stack" of multifunctional materials (e.g., where the stack includes, for example, particles having a gradient structure that balances the transport of ions and electrons for improved power capability, energy density, and life; a bifunctional cathode additive that simultaneously stores lithium and conducts electrons, replacing expensive and space-consuming carbon; a binding molecule that spatially confines the electrochemical reaction that stores energy and thereby extends life; an electrolyte component that improves the basic efficiency of the electrolyte, thereby providing improved energy density; and / or a cathode design that enables higher safety and energy density); (b) a compact electrode layer; (c) a compact tertiary structure; (d) porosity control; (e) a core-shell structure; (f) a cross-linked polymer shell; (g) a self-doped polymer shell; (h) an ion-conducting binder; (i) a double-layer hybrid cathode; (j) a polymer that captures polysulfides; (k) a three-dimensional structure with a high surface area (e.g., accommodating both carbon and lithium, e.g., embedding); and (l) a three-dimensional structure in which carbon is replaced by a metal disulfide (e.g., and where the battery includes a polymer electrolyte for sulfur).
[0082] anode
[0083] In certain embodiments, the secondary sulfur battery includes a lithium anode. Any lithium anode suitable for a lithium-sulfur battery can be used. In certain embodiments, the anode of the secondary sulfur battery comprises a negative electrode active material selected from a material in which lithium is reversibly embedded, a material that reacts with lithium ions to form a lithium-containing compound, metallic lithium, a lithium alloy, and a combination thereof. In certain embodiments, the anode comprises metallic lithium. In certain embodiments, the lithium-containing anode composition comprises a carbon-based compound. In certain embodiments, the carbon-based compound is selected from the group consisting of crystalline carbon, amorphous carbon, graphite, and mixtures thereof. In certain embodiments, the anode contains no carbon or contains a small amount of carbon (e.g., not more than 5.0 wt. %, not more than 3.0 wt. %, not more than 2.0 wt. %, not more than 1.0 wt. %, or not more than 0.5 wt. %). In certain embodiments, the material that reacts with lithium ions to form a lithium-containing compound is selected from tin oxide (SnO 2), titanium nitrate and silicon. In certain embodiments, the lithium alloy comprises an alloy of lithium and another alkali metal (e.g., sodium, potassium, rubidium or cesium). In certain embodiments, the lithium alloy comprises an alloy of lithium and a transition metal. In certain embodiments, the lithium alloy comprises an alloy of lithium and a metal selected from the group consisting of: Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Ba, Ra, Al, Sn, In, Zn, Sm, La and combinations thereof. In certain embodiments, the lithium alloy comprises an alloy of lithium and indium. In certain embodiments, the lithium alloy comprises an alloy of lithium and aluminum. In certain embodiments, the lithium alloy comprises an alloy of lithium and zinc. In certain embodiments, the anode comprises a lithium-silicon alloy. Examples of suitable lithium-silicon alloys include: Li 15 Si 4 , Li 12 Si 7 , Li 7 Si 3 , Li 13 Si 4 and Li 21 Si 5 / Li 22 Si 5 In certain embodiments, the lithium metal or lithium alloy is present in the form of a composite material with another material. In certain embodiments, such composite materials include materials such as graphite, graphene, metal sulfides or oxides, or conductive polymers.
[0084] In some embodiments, the anode is protected from redox shuttle reactions and dangerous runaway reactions by any method reported in the art, for example, by chemical passivation or by creating a protective layer on the anode surface by deposition or polymerization. For example, in certain embodiments, the anode comprises an inorganic protective layer, an organic protective layer, or a mixture thereof on the surface of lithium metal. In certain embodiments, the inorganic protective layer comprises Mg, Al, B, Sn, Pb, Cd, Si, In, Ga, lithium silicate, lithium borate, lithium phosphate, lithium phosphitride, lithium silicon sulfide, lithium borosulfide, lithium aluminum sulfide, lithium phosphosulfide, lithium fluoride, or a combination thereof. In certain embodiments, the organic protective layer comprises a conductive monomer, oligomer, or polymer. In certain embodiments, this polymer is selected from poly (p-phenylene), polyacetylene, poly (p-phenylene vinylene), polyaniline, polypyrrole, polythiophene, poly (2,5-ethylene vinylene), acetylene, poly (o-naphthalene), polyphenylene and poly (naphthalene-2,6-di-base), or a combination thereof.
[0085] In addition, in certain embodiments, during the charge and discharge of the secondary sulfur battery, the inactive sulfur material generated from the electroactive sulfur material of the cathode is attached to the surface of the anode. As used herein, the term "inactive sulfur" refers to sulfur that is not active in repeated electrochemical reactions and chemical reactions, so that it cannot participate in the electrochemical reactions of the cathode. In certain embodiments, the inactive sulfur on the surface of the anode acts as a protective layer on such an electrode. In certain embodiments, the inactive sulfur is lithium sulfide.
[0086] In some embodiments, the battery is a primary cell or a low cycle life battery. Such a battery may include an anode, a cathode (e.g., comprising a cathode material disclosed herein), an electrolyte, and an optional separator. The cathode may be suitable for a secondary battery. Nevertheless, the battery may be a primary cell or a low cycle life battery because, for example, the anode degrades irreversibly during discharge (e.g., in one or a few cycles).
[0087] It is further contemplated that the present disclosure may be applicable to sodium-sulfur batteries. Such sodium-sulfur batteries include a sodium-based anode and are encompassed within the scope of the present disclosure.
[0088] It is further contemplated that the present disclosure may be applicable to cells having an anode-free configuration. In certain embodiments, the cell has an anode-free configuration and includes one or more of: (a) a thin layer of garnet, (b) a structure (e.g., a complex 3D structure) having a coating deposited by atomic layer deposition (ALD) (e.g., wherein the ALD coating includes one or more members selected from the group consisting of lithium phosphorus oxynitride (LiPON), garnet, oxide, perovskite, sulfide, Li 3 BO 3 -Li 2 CO 3 (LBCO), sodium superionic conductor (NASICON), and alumina); (c) polymers (e.g., polyethylene oxide (PEO) or block copolymers); (d) lithium phosphorus oxynitride (LiPON), and (e) solid electrolyte interface (SEI) layers (e.g., artificial SEI layers formed in situ).
[0089] Electrode preparation
[0090] There are many methods for making electrodes for secondary sulfur batteries. One process, such as a "wet process", involves adding a solid cathode material to a liquid to prepare a slurry composition. These slurries are generally in the form of a viscous liquid that is formulated to facilitate downstream coating operations. Thorough mixing of the slurry may be very important for coating and drying operations, which can affect the performance and quality of the electrode. Suitable mixing devices include ball mills, magnetic stirrers, ultrasonic stirrers, planetary mixers, high-speed mixers, homogenizers, universal mixers, and static mixers. The liquid used to prepare the slurry can be a liquid that evenly disperses the active material, binder, conductive material, and any additives and is easily evaporated. Suitable slurry liquids include, for example, N-methylpyrrolidone, acetonitrile, methanol, ethanol, propanol, butanol, tetrahydrofuran, water, isopropanol, dimethylpyrrolidone, propylene carbonate, γ-butyrolactone, and the like.
[0091] In some embodiments, the prepared composition is coated on a current collector and dried to form an electrode. Specifically, the slurry is used to coat the conductor to form an electrode by evenly spreading the slurry on the conductor, and then in some embodiments, optionally rolling (e.g., calendering) and heating, as known in the art. Generally speaking, the matrix of active material and conductive material is combined together and fixed to the conductor by an adhesive. In some embodiments, the matrix comprises a polymer adhesive, such as polyvinylidene fluoride (PVDF), poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF / HFP), polytetrafluoroethylene (PTFE), Kynar 2801, Powerflex LBG, HSV 900, Styrene butadiene rubber (SBR), polyethylene oxide (PEO) or polytetrafluoroethylene (PTFE). In certain embodiments, additional carbon particles, carbon nanofibers, carbon nanotubes are dispersed in the matrix to improve conductivity. Alternatively or additionally, in certain embodiments, a lithium salt is dispersed in the matrix to improve lithium conductivity.
[0092] In certain embodiments, the current collector is selected from the group consisting of aluminum foil, copper foil, nickel foil, stainless steel foil, titanium foil, zirconium foil, molybdenum foil, nickel foam, copper foam, carbon paper or carbon fiber sheet, polymer substrate coated with conductive metal, and / or combinations thereof.
[0093] PCT Publication Nos. WO2015 / 003184, WO2014 / 074150, and WO2013 / 040067, the entire disclosures of which are hereby incorporated by reference herein, describe various methods of making electrodes and electrochemical cells.
[0094] Partition
[0095] In certain embodiments, the secondary sulfur battery includes a separator that separates the anode and cathode and prevents direct electronic conduction between them. In certain embodiments, the separator has high lithium ion permeability. In certain embodiments, the separator has relatively low permeability to polysulfide ions dissolved in the electrolyte. In certain such embodiments, the separator as a whole inhibits or limits the passage of electrolyte-soluble sulfides between the anode portion and the cathode portion of the battery. In certain embodiments, the separator of the impermeable material is constructed to allow lithium ions to be transmitted between the anode and cathode of the battery during battery charging and discharging. In some such embodiments, the separator is porous. One or more electrolyte permeable channels that bypass or penetrate the holes in the impermeable surface of the separator can be provided to allow sufficient lithium ion flux between the anode portion and the cathode portion of the battery.
[0096] Those skilled in the art will appreciate that the optimum size of the separator must balance competing imperatives: maximally hindering polysulfide migration while allowing adequate lithium ion flux. The shape and orientation of the separator are not particularly limited other than the considerations described and depend in part on the cell configuration. For example, in some embodiments, the separator in a coin cell is substantially circular, while the separator in a pouch cell is substantially rectangular. In some embodiments, the separator is substantially flat. However, it is not excluded that a curved or other non-planar configuration may be used.
[0097] The separator can have any suitable thickness. In order to maximize the energy density of the battery, it is generally preferred that the separator is as thin and light as possible. However, the separator should be thick enough to provide sufficient mechanical robustness and ensure suitable electrical separation of the electrodes. In certain embodiments, the thickness of the separator is from about 1 μm to about 200 μm, preferably from about 5 μm to about 100 μm, and more preferably from about 10 μm to about 30 μm.
[0098] Electrolytes
[0099] In certain embodiments, the secondary sulfur battery includes an electrolyte comprising an electrolyte salt. Examples of electrolyte salts include, for example, lithium trifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium perchlorate, LiPF 6 , LiBF 4 , tetraalkylammonium salts (e.g., tetrabutylammonium tetrafluoroborate, TBABF 4 ), salts that are liquid at room temperature (e.g., imidazolium salts, such as 1-ethyl-3-methylimidazolium bis-(perfluoroethylsulfonyl)imide, EMIBeti), and the like.
[0100] In certain embodiments, the electrolyte comprises one or more alkali metal salts. In certain embodiments, such salts include lithium salts such as LiCF 3 SO3 、LiClO 4 、LiNO 3 、LiPF 6 , LiBr, LiTDI, LiFSI and LiTFSI, or a combination thereof. In certain embodiments, the electrolyte comprises an ionic liquid such as 1-ethyl-3-methylimidazolium-TFSI, N-butyl-N-methylpiperidinium-TFSI, N-methyl-n-butylpyrrolium-TFSI and N-methyl-N-propylpiperidinium-TFSI, or a combination thereof. In certain embodiments, the electrolyte comprises a superionic conductor such as a sulfide, an oxide and a phosphate, for example phosphorus pentasulfide, or a combination thereof.
[0101] In certain embodiments, the electrolyte is a liquid. For example, in certain embodiments, the electrolyte comprises an organic solvent. In certain embodiments, the electrolyte comprises only one organic solvent. In some embodiments, the electrolyte comprises a mixture of two or more organic solvents. In certain embodiments, the organic solvent mixture comprises one or more weak polar solvents, strong polar solvents, and lithium protection solvents.
[0102] As used herein, the term "weak polar solvent" is defined as a solvent that can dissolve elemental sulfur and has a dielectric constant of less than 15. Weak polar solvents are selected from aromatic compounds, bicyclic ethers, and acyclic carbonate compounds. Examples of weak polar solvents include xylene, dimethoxyethane, 2-methyltetrahydrofuran, diethyl carbonate, dimethyl carbonate, toluene, dimethyl ether, diethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, etc. As used herein, the term "strong polar solvent" is defined as a solvent that can dissolve lithium polysulfide and has a dielectric constant greater than 15. Strong polar solvents are selected from bicyclic carbonate compounds, sulfoxide compounds, lactone compounds, ketone compounds, ester compounds, sulfate compounds, and sulfite compounds. Examples of strong polar solvents include hexamethylphosphorus triamide, γ-butyrolactone, acetonitrile, ethylene carbonate, propylene carbonate, N-methylpyrrolidone, 3-methyl-2-oxazolidinone, dimethylformamide, cyclopentane, dimethylacetamide, dimethyl sulfoxide, dimethyl sulfate, ethylene glycol diacetate, dimethyl sulfite, ethylene glycol sulfite, etc. As used herein, the term "lithium protection solvent" is defined as a solvent that forms a good protective layer (i.e., a stable solid electrolyte interface (SEI) layer) on the lithium surface and exhibits a circulation efficiency of at least 50%. The lithium protection solvent is selected from saturated ether compounds, unsaturated ether compounds, and heterocyclic compounds containing one or more heteroatoms selected from the group consisting of N, O and / or S. Examples of lithium protection solvents include tetrahydrofuran, 1,3-dioxolane, 3,5-dimethylisoxazole, 2,5-dimethylfuran, furan, 2-methylfuran, 1,4-oxacyclohexane, 4-methyldioxolane, etc.
[0103] In certain embodiments, the electrolyte is a liquid (e.g., an organic solvent). In some embodiments, the liquid is selected from the group consisting of organic carbonates, ethers, sulfones, water, alcohols, fluorocarbons, or a combination of any of these substances. In certain embodiments, the electrolyte comprises an ether solvent.
[0104] In certain embodiments, the organic solvent comprises an ether. In certain embodiments, the organic solvent is selected from the group consisting of: 1,3-dioxolane, dimethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, γ-butyrolactone, γ-valerolactone, and combinations thereof. In certain embodiments, the organic solvent comprises a mixture of 1,3-dioxolane and dimethoxyethane. In certain embodiments, the organic solvent comprises a 1:1 volume / volume mixture of 1,3-dioxolane and dimethoxyethane. In certain embodiments, the organic solvent is selected from the group consisting of: diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, γ-butyrolactone, γ-valerolactone, and combinations thereof. In certain embodiments, the electrolyte comprises sulfolane, sulfone, dimethyl sulfone, methyl ethyl sulfone, or a combination thereof. In some embodiments, the electrolyte comprises ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, or a combination thereof.
[0105] In certain embodiments, the electrolyte is solid. In certain embodiments, the solid electrolyte comprises a polymer. In certain embodiments, the solid electrolyte comprises glass, ceramic, inorganic composite material, or a combination thereof. In certain embodiments, the solid electrolyte comprises a polymer composite material with glass, ceramic, inorganic composite material, or a combination thereof. In certain embodiments, such solid electrolytes comprise one or more liquid components as a plasticizer or form a "gel electrolyte".
[0106] Secondary sulfur battery
[0107] Secondary sulfur batteries including the above-described cathode compositions are described herein. For example, in certain embodiments, such batteries include a lithium-containing anode composition coupled to a provided cathode composition via a lithium-conducting electrolyte. In some embodiments, such batteries also include additional components such as a separator between the anode and cathode, anode and cathode current collectors, terminals that can couple the battery to an external load, and packaging such as a flexible bag or a rigid metal container. It is further contemplated that the present disclosure regarding secondary sulfur batteries can be applied to sodium-sulfur batteries, and such batteries are also considered to be within the scope of certain embodiments of the present disclosure.
[0108] Figure 2A cross section of an electrochemical cell 800 according to an exemplary embodiment of the present disclosure is illustrated. The electrochemical cell 800 includes a negative electrode 802, a positive electrode 804, a separator 806 between the negative electrode 802 and the positive electrode 804, a container 810, and a fluid electrolyte 812 in contact with the negative electrode 802 and the positive electrode 804. Such a cell optionally includes additional electrode layers and separators 802a, 802b, 804a, 804b, 806a, and 806b.
[0109] The negative electrode 802 (sometimes also referred to herein as the anode) comprises a negative electrode active material that can accept cations. Non-limiting examples of negative electrode active materials for lithium-based electrochemical cells include lithium metal, lithium alloys (such as Si, Sn, Bi, In and / or Al alloys), Li 4 Ti 5 O 12 , hard carbon, graphite carbon, metal chalcogenide and / or amorphous carbon. According to some embodiments of the present disclosure, when the electrochemical cell 800 is initially manufactured, a majority (e.g., greater than 90 wt%) of the anode active material may be initially contained in the discharge positive electrode 804 (also sometimes referred to as the cathode), such that the electrode active material forms part of the first electrode 802 during the first charge of the electrochemical cell 800.
[0110] One technique for depositing electroactive material on a portion of negative electrode 802 is described in U.S. Patent Publication Nos. 2016 / 0172660 and 2016 / 0172661 (in the name of Fischer et al.), the contents of each of which are hereby incorporated by reference herein to the extent such contents are not inconsistent with the present disclosure.
[0111] Positive electrode 804 (also referred to herein as cathode) comprises a cathode composition as described herein. In certain embodiments, the cathode composition comprises about 30 to about 70% by weight of electroactive sulfur. In certain embodiments, the cathode comprises at least about 70% of the total sulfur present in the electrochemical cell. In certain embodiments, the cathode comprises at least about 80% of the total sulfur present in the electrochemical cell. In certain embodiments, the cathode comprises at least about 90% of the total sulfur present in the electrochemical cell. In certain embodiments, the cathode comprises at least about 95% of the total sulfur present in the electrochemical cell. In certain embodiments, the cathode comprises at least about 99% of the total sulfur present in the electrochemical cell. In certain embodiments, the cathode comprises substantially all of the total sulfur present in the electrochemical cell.
[0112] Negative electrode 802 and positive electrode 804 may also include one or more conductive additives as described herein. According to some embodiments of the present disclosure, negative electrode 802 and / or positive electrode 804 also include one or more polymer binders as described herein.
[0113] Figure 3 Examples of batteries according to various embodiments described herein are illustrated. For illustrative purposes, cylindrical batteries are shown here, but other types of arrangements, including square batteries or pouch (laminated) batteries, may also be used as desired. Example lithium battery 901 includes a negative electrode 902, a positive electrode 904, a separator 906 between the negative electrode 902 and the positive electrode 904, an electrolyte (not shown) impregnating the separator 906, a battery shell 905, and a seal 908 sealing the battery shell 905. It should be understood that the example battery 901 can embody multiple aspects of the present disclosure in various designs at the same time.
[0114] The secondary sulfur battery of the present disclosure includes a lithium anode, a porous sulfur-based cathode, and an electrolyte that allows lithium ions to be transported between the anode and the cathode. In certain embodiments described herein, the anode portion of the battery comprises an anode and a portion of the electrolyte in contact with it. Similarly, in certain embodiments described herein, the cathode portion of the battery comprises a cathode and a portion of the electrolyte in contact with it. In certain embodiments, the battery includes a lithium ion permeable separator that defines a boundary between the anode portion and the cathode portion. In certain embodiments, the battery includes a housing that surrounds the anode portion and the cathode portion. In certain embodiments, the battery housing includes a conductive anode end cap electrically connected to the anode and a conductive cathode end cap electrically connected to the cathode to facilitate charging and discharging via an external circuit.
[0115] In certain embodiments, the secondary sulfur batteries of the present disclosure are defined according to the ratio of their electrolyte to electroactive sulfur. The electrolyte volume and the ratio of electrolyte to sulfur in the cathode (volume / weight) are related to the energy density of the sulfur battery. The electrolyte can be distributed in different volumes within the battery, for example, the electrolyte can be contained in the pores of the cathode, in the separator, and in contact with the anode or in the anode solid electrolyte interphase. The electrolyte can also be contained in other spaces within the battery that are not in direct contact with the anode or cathode active materials-for example, the electrolyte can be retained in an annular volume at the edge of a coin cell. In certain embodiments, the present disclosure provides batteries in which all or most of the electrolyte is contained within the cathode. Preferably, substantially all of the electrolyte is contained within the cathode, and only the minimum amount of electrolyte required to wet the separator and the anode surface or SEI is located outside the cathode. The electrolyte contained within the cathode is referred to as the "contained electrolyte" and its volume V CE It can be estimated as the theoretical pore volume, or porosity multiplied by the geometric volume of the cathode membrane:
[0116] V CP = P% × area × thickness 阴极
[0117] In certain embodiments, provided secondary sulfur batteries are characterized by a total electrolyte inventory (V tot) is contained in the cathode (e.g., V CE / V tot >0.5). In certain embodiments, provided secondary sulfur batteries are characterized by a total electrolyte inventory (V tot ) is contained in the cathode (e.g., V CE / V tot >0.8). In certain embodiments, the secondary sulfur battery has at least 60%, at least 65%, or at least 70% of the electrolyte contained in the cathode porosity. In certain embodiments, the secondary sulfur battery has at least 80%, at least 85%, or at least 90% of the electrolyte contained in the cathode porosity. In certain embodiments, the secondary sulfur battery has at least 92%, at least 94%, at least 95%, at least 96%, or at least 97% of the electrolyte contained in the cathode.
[0118] The total electrolyte to sulfur ratio (E / S) is another parameter that affects the battery energy density. The E / S ratio is based on the total electrolyte volume V tot and the mass of electroactive sulfur (m 硫 ) calculated as:
[0119]
[0120] In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is equal to or less than about 6 microliters of electrolyte per milligram of electroactive sulfur. In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is equal to or less than about 5 microliters of electrolyte per milligram of electroactive sulfur. In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is equal to or less than about 4.5 microliters of electrolyte per milligram of electroactive sulfur. In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is equal to or less than about 3.5 microliters of electrolyte per milligram of electroactive sulfur or less than about 3.0 microliters of electrolyte per milligram of electroactive sulfur. In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is equal to or less than about 3.5 microliters of electrolyte per milligram of electroactive sulfur. In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is equal to or less than about 3 microliters of electrolyte per milligram of electroactive sulfur. In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is between about 1.8 and about 3.5 μL / mg S. In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is between about 1.8 and about 2.5 μL / mg S.
[0121] Core-shell nanostructures
[0122] In certain embodiments, cathode material has core-shell structure (for example, nanostructure), wherein core contains sulfur active material and the shell around it contains non-sulfur electroactive material. In certain embodiments, the structure is nanoporous. In certain embodiments, the average diameter of core is, for example, less than about 1000nm, less than about 500nm, less than about 250nm, less than about 100nm, less than about 80nm, less than about 70nm, less than about 60nm, less than about 50nm, less than about 40nm, less than about 30nm, less than about 25nm, less than about 20nm, less than about 10nm or less than about 5nm, and / or the average diameter of core can be between any two of the above listed values in any range. In certain embodiments, the shape of core is spherical, coarse spherical or amorphous. In certain embodiments, the average diameter of core is between about 50 to about 500nm, between about 50 to about 200nm, between about 20 to about 100nm, between about 100 to about 300nm or between about 200 to about 400nm.
[0123] In certain embodiments, the average thickness of the shell around the core is, for example, less than about 1000nm, less than about 500nm, less than about 250nm, less than about 100nm, less than about 80nm, less than about 70nm, less than about 60nm, less than about 50nm, less than about 40nm, less than about 30nm, less than about 25nm, less than about 20nm, less than about 15nm, less than about 10nm, less than about 5nm, less than about 3nm, less than about 2nm or less than about 1nm, and / or the average thickness of the shell can be in any range between any two of the above listed values. In certain embodiments, the average thickness of the shell around the core is between about 1 to about 50nm, between about 2 to about 20nm, between about 1 to about 10nm, between about 10 to about 20nm, between about 5 to about 15nm or between about 1 to about 5nm.
[0124] In certain embodiments, the core of the provided core-shell particles consists of a substantially pure electroactive sulfur material. In certain embodiments, the core comprises a composite material of an electroactive sulfur material and an additional material (such as an inorganic solid, metal, polymer or other non-sulfur electroactive material). Such composite materials may comprise a simple physical mixture of materials or a more complex structural composite material, such as a porous scaffold infused with a sulfur electroactive material.
[0125] In certain embodiments, the non-sulfur electroactive shell of the provided core-shell particles is non-porous and / or substantially impermeable to liquids (e.g., electrolytes) and / or impermeable to sulfur or polysulfides (or mixtures of electrolytes and polysulfides). This arrangement may be advantageous because it allows electrons and lithium ions to enter the electroactive sulfur core while preventing the electroactive sulfur material from being redistributed in the cathode or battery.
[0126] In other embodiments, the non-sulfur electroactive shell of the core-shell particles provided is porous and / or permeable (e.g., permeable to a liquid electrolyte or its components). In certain embodiments, such permeable shells may be useful for ensuring that the electrolyte is in contact with the electroactive sulfur and / or preventing physical strains caused by volume changes in the core from rupturing or otherwise damaging the shell. In certain embodiments, such shells are nanoporous; for example, having a pore diameter less than 1 nm; for example, less than 0.5 nm, less than 0.4 nm, or less than 0.3 nm, or less than 0.2 nm, and / or the average pore size is within any range between any two of the values listed above. In certain embodiments, the average pore size of the core and / or shell is less than 1 nm; for example, less than 0.9 nm, less than 0.8 nm, less than 0.7 nm, or less than 0.6 nm, and / or the average pore size is within any range between any two of the values listed above. In certain embodiments, the pore size is measured by a microscope (e.g., TEM, SEM, or AFM).
[0127] In certain embodiments, the electroactive sulfur material comprises S 8 Sulfur in the form of cyclic octaatomic molecules, lithium sulfide (e.g., Li 2 S 2 and / or Li 2 In some embodiments, the non-sulfur electroactive blend comprises one or more non-sulfur chalcogenides.
[0128] In certain embodiments, the chalcogenide has at least one chalcogen anion (oxygen, sulfur, selenium, tellurium, or polonium anion) and at least one electropositive element. In certain embodiments, the chalcogenide may be based on a sulfide, selenide, or telluride. In certain embodiments, the chalcogenide comprises a metal sulfide (e.g., a sulfide of a metal other than lithium or sodium). In certain embodiments, one or more chalcogenides comprise a transition metal sulfide. In certain embodiments, one or more chalcogenides comprise one or more of the following: TiS 2 、LiTiS 2 (LTS), VS 2 、MoS 2 、Mo 6 S 8 and NbSe 3 In certain embodiments, the one or more chalcogenides include transition metal oxides and / or polyanionic compounds. In certain embodiments, the one or more chalcogenides include metal monochalcogenides having the formula MX, wherein M is a transition metal and X is S, Se, or Te. In certain embodiments, the one or more chalcogenides include at least one of the formula MX 2A transition metal dichalcogenide (TMD) wherein M is a transition metal (e.g., Ti, V, Co, Ni, Zr, Nb, Mo, Tc, Rh, Pd, Hf, Ta, W, Re, Ir, or Pt), and wherein X is S, Se, or Te. In certain embodiments, the one or more chalcogenides include materials having a layered crystal structure (e.g., LiTiS 2 、LiCoO 2 、LiNiO 2 、LiMnO 2 、LiNi 0.33 Mn 0.33 Co 0.33 O 2 、LiNi 0.8 Co 0.15 Al 0.05 O 2 or Li 2 MnO 3 ) and / or materials having a spinel crystal structure (e.g., LiMn 2 O 4 or LiCo 2 O 4 In certain embodiments, the cathode material comprises LiFePO 4 、LiMnPO 4 or LiCoPO 4 (e.g., having an olivine crystal structure) and / or LiFeSO 4 F or LiVPO 4 F (e.g., having a ferroxite crystal structure). Throughout the specification, where articles, devices, and systems are described as having, including, or comprising particular components, or where processes and methods are described as having, including, or comprising particular steps, it is additionally contemplated that there are articles, devices, and systems according to certain embodiments of the present disclosure that consist essentially of or consist of the recited components, and that there are processes and methods according to certain embodiments of the present disclosure that consist essentially of or consist of the recited processing steps. "Sulfur electroactive material" and "electroactive sulfur material" are used interchangeably herein.
[0129] It should be understood that the order of steps or the order in which certain actions are performed is not important, as long as operability is not lost. In addition, two or more steps or actions can be performed simultaneously. As understood by those skilled in the art, the terms "over / above / on" and "under / below / beneath" are relative terms and can be interchanged with reference to the different orientations of the layers, elements and substrates included in the present disclosure. For example, the first layer on the second layer means in some embodiments that the first layer is directly on the second layer and in contact with the second layer. In other embodiments, the first layer on the second layer can include another layer therebetween.
[0130] Headings are provided for the convenience of the reader—the presence and / or placement of headings is not intended to limit the scope of the subject matter described herein.
[0131] Equivalent solutions
[0132] It is contemplated that the systems, apparatuses, methods, and processes of the present disclosure encompass variations and adaptations developed using information from the embodiments described herein.Adaptations and / or modifications of the systems, apparatuses, methods, and processes described herein may be performed by one of ordinary skill in the relevant art.
[0133] Certain embodiments of the present disclosure are described above. However, it is expressly pointed out that the present disclosure is not limited to those embodiments, but additions and modifications to the contents explicitly described in the present disclosure are also intended to be included within the scope of the present disclosure. In addition, it should be understood that the features of the various embodiments described in the present disclosure are not mutually exclusive, and may exist in various combinations and arrangements without departing from the spirit and scope of the present disclosure, even if these combinations or arrangements have not been expressed. The present disclosure has been described in detail with specific reference to certain embodiments of the present disclosure, but it should be understood that changes and modifications may be achieved within the spirit and scope of the claimed invention.
Claims
1. A cathode material comprising a mixture of the following substances: a first active material comprising at least one electroactive sulfur material; and a second non-sulfur active material comprising a blend of two or more non-sulfur electroactive materials (e.g., metal chalcogenides, transition metal oxides and / or polyanionic compounds), the blend being selected such that the voltage plateau of the discharge voltage curve of the blend is close to the discharge voltage curve of the at least one electroactive sulfur material [e.g., wherein the cathode material is at least 10% by mass of non-sulfur electroactive material (e.g., metal chalcogenide) relative to sulfur (e.g., 10 to 90% by mass of non-sulfur electroactive material, e.g., 30 to 70% by mass of non-sulfur electroactive material)].
2. The cathode material of claim 1, wherein the voltage curves of the first active material and the second active material are individually measured under similar electrochemical conditions to evaluate whether they are close to each other.
3. The cathode material of claim 1 or 2, wherein the blend of two or more non-sulfur electroactive materials has a discharge voltage profile characterized by a discharge voltage attributable to the blended non-sulfur material being within 10% (e.g., within 5%, within 3%, or within 1%) of the sulfur discharge voltage attributable to the at least one electroactive sulfur material for at least 50% of the total discharge (e.g., for at least 60%, at least 75%, or at least 80% of the total discharge).
4. A cathode material as described in any of the preceding claims, wherein the at least one electroactive sulfur material comprises at least one of the following (i) to (iv): (i) sulfur in the form of an S8 cyclic octaatomic molecule, (ii) sulfur in the form of a lithium sulfide (e.g., Li2S2 and / or Li2S), (iii) sulfur in the form of an electroactive organic sulfur compound, and (iv) sulfur in the form of an electroactive sulfur-containing polymer.
5. A cathode material as described in any of the preceding claims, wherein each of the two or more non-sulfur electroactive materials (e.g., intercalation materials) has a separate discharge voltage curve having a voltage plateau that is different from the voltage plateau of the separate discharge voltage curve of any other material in the two or more non-sulfur electroactive materials.
6. The cathode material of any of the preceding claims, wherein the blend of two or more non-sulfur electroactive materials comprises one or more chalcogenides (e.g., wherein each of the two or more non-sulfur electroactive materials is a chalcogenide) (e.g., comprises one or more metal chalcogenides, such as one or more metal sulfides).
7. The cathode material of claim 6, wherein each of the two or more non-sulfur electroactive materials (i) has a different crystal structure (e.g., layered, spinel, olivine, ferroxene), (ii) has a different composition, or (iii) has both (i) and (ii).
8. The cathode material of any one of the preceding claims, wherein the second non-sulfur active material has a discharge voltage curve having two plateaus.
9. The cathode material of claim 8, wherein one of the two plateaus corresponds to a soluble / intermediate polysulfide conversion and the other of the two plateaus corresponds to a solid or quasi-solid product.
10. The cathode material of any of the preceding claims, wherein the second non-sulfur active material has a discharge voltage curve close to the discharge voltage curve of sulfur to lithium sulfide (eg, S8→Li2S).
11. The cathode material of any one of claims 8 to 10, wherein the discharge voltage curve having two plateaus has a voltage of about 2.2 to about 2.4 V relative to Li / Li. + ) range and about 2.0 to about 2.2 (V, relative to Li / Li + ) within the scope of the second platform.
12. A cathode material comprising: An electroactive sulfur material [e.g., at least one of the following (i) to (iv): (i) sulfur in the form of a S8 cyclic octaatomic molecule, (ii) sulfur in the form of a lithium sulfide (e.g., Li2S2 and / or Li2S), (iii) sulfur in the form of an electroactive organic sulfur compound, and (iv) sulfur in the form of an electroactive sulfur-containing polymer] [e.g., at least one of (i) sulfur (S8) and (ii) lithium sulfide (e.g., Li2S2 and / or Li2S)]; and Two or more non-sulfur electroactive materials [eg, intercalation materials (eg, lithium intercalation materials)], wherein the two or more electroactive materials together have a discharge voltage profile having at least two distinct voltage plateaus.
13. The cathode material of claim 12, wherein the two or more non-sulfur electroactive materials together have a discharge voltage curve that corresponds to the discharge voltage curve of sulfur (e.g., each of the two or more electroactive materials has a discharge voltage curve having a voltage plateau that corresponds to the voltage plateau of the discharge voltage curve of sulfur).
14. The cathode material of claim 12 or 13, wherein each of the two or more non-sulfur electroactive materials has a separate discharge voltage curve having a voltage plateau that is different from the voltage plateau of the separate discharge voltage curve of any other of the two or more non-sulfur electroactive materials.
15. The cathode material of any one of claims 12 to 14, wherein the voltage plateau of the individual discharge voltage curve of each of the two or more electroactive materials is within 10% (e.g., within 5%, within 3%, or within 1%) of the corresponding voltage plateau of the discharge voltage curve of the sulfur.
16. A cathode material as claimed in any preceding claim comprising a core-shell structure.
17. The cathode material of claim 16, wherein the core-shell structure comprises a core each having a surrounding shell, the core comprising the electroactive sulfur material (e.g., S8, Li2S2 and / or Li2S), and the shell comprising at least one of the two or more non-sulfur electroactive materials (e.g., one or more metal chalcogenides).
18. The cathode material of claim 16 or 17, wherein the core-shell structure has an average core diameter in the range of 50 to 300 nm and an average shell thickness in the range of 1 to 20 nm thick (eg, no more than 10 nm thick).
19. The cathode material of any one of claims 16 to 18, wherein the core-shell structure has at least 10 mass % of non-sulfur electroactive material (e.g., metal sulfide) relative to sulfur (e.g., 10 to 90 mass % of non-sulfur, non-carbon electroactive material, e.g., 30 to 70 mass % of non-sulfur, non-carbon electroactive material).
20. A battery comprising (i) a cathode comprising a cathode material according to any one of the preceding claims, and (ii) an electrolyte (eg, a solid state electrolyte (SSE)) in contact with the cathode.
21. The battery of claim 20, further comprising an anode.
22. The battery of claim 21, wherein the anode is a protected lithium metal anode.
23. The battery of claim 20, further comprising a protected current collector.
24. A method of operating a lithium-sulfur battery, the lithium-sulfur battery comprising a cathode, the cathode comprising (i) sulfur or lithium sulfide (e.g., Li2S2 and / or Li2S) (e.g., both sulfur and lithium sulfide), (ii) a first non-sulfur electroactive material (e.g., a first intercalation material), and (iii) a second non-sulfur electroactive material different from the first non-sulfur electroactive material (e.g., a second intercalation material), the method comprising discharging the battery by: Simultaneously inserting (e.g., intercalating) lithium into the first non-sulfur electroactive material while at least partially converting at least a portion of the sulfur or lithium sulfide (e.g., S8→Li2S) at a first voltage; and Lithium is then simultaneously inserted (e.g., intercalated) into the second non-sulfur electroactive material while at least partially (e.g., further) converting at least a portion of the sulfur of the lithium sulfide (e.g., S8→Li2S) at a second voltage different from the first voltage.
25. The method of claim 24, comprising charging the battery after discharging the battery, wherein charging the battery comprises: Simultaneously (i) removing lithium from the first non-sulfur electroactive material, (ii) removing lithium from the second non-sulfur electroactive material, and (iii) at least partially converting at least a portion of the sulfur or lithium sulfide (e.g., Li2S→S8) at a third voltage (e.g., different from the first voltage and the second voltage).
26. A method of operating a battery, the battery comprising a cathode, the cathode comprising (i) a sulfur electroactive material, (ii) a first non-sulfur electroactive material (e.g., a first intercalation material), and (iii) a second non-sulfur electroactive material different from the first non-sulfur electroactive material (e.g., a second intercalation material), the method comprising discharging the battery by: simultaneously inserting (e.g., intercalating) ions (e.g., lithium) into the first non-sulfur electroactive material while at least partially converting at least a portion of the sulfur electroactive material at a first voltage; and Subsequently, ions (e.g., lithium) are simultaneously inserted (e.g., intercalated) into the second non-sulfur electroactive material while at least partially (e.g., further) converting at least a portion of the sulfur electroactive material [e.g., at least a portion of lithium sulfide (e.g., S8→Li2S)] at a second voltage different from the first voltage.
27. The method of claim 26, comprising charging the battery after discharging the battery, wherein charging the battery comprises: Simultaneously (i) removing ions from the first non-sulfur electroactive material, (ii) removing ions from the second non-sulfur electroactive material, and (iii) at least partially converting at least a portion of the sulfur electroactive material [e.g., sulfur or lithium sulfide (e.g., Li2S→S8)] at a third voltage (e.g., different from the first voltage and the second voltage).
28. A solid-state sulfur battery comprising: anode; solid electrolyte; and A cathode, the cathode comprising: a first active material, the first active material comprising at least one electroactive sulfur material; as well as One or more non-sulfur electroactive materials (e.g., metal chalcogenides, transition metal oxides, and / or polyanionic compounds), wherein the discharge voltage curve of the one or more non-sulfur electroactive materials is close to at least a portion of the discharge voltage curve of the at least one electroactive sulfur material [e.g., wherein the cathode material is at least 10% by mass of non-sulfur electroactive material (e.g., metal chalcogenide) relative to sulfur (e.g., 10 to 90% by mass of non-sulfur electroactive material, e.g., 30 to 70% by mass of non-sulfur electroactive material)].
29. The battery of claim 28, wherein the one or more non-sulfur electroactive materials are a blend of two or more non-sulfur electroactive materials.
30. The battery of claim 29, wherein at least a portion of the discharge voltage curve comprises two or more distinct portions, each portion corresponding to one of the two or more non-sulfur electroactive materials.
31. The battery of claim 28, wherein the one or more non-sulfur electroactive materials comprise (eg, are) mixed metal sulfides.
32. The battery of any one of claims 28 to 31, wherein at least a portion of the discharge voltage curve exists in a voltage range of 2.5V to 1.9V (e.g., 2.3V to 2.1V) and / or a SoC range of 90% to 30% (e.g., 90% to 60%).
33. The battery of any one of claims 28 to 32, wherein at least a portion of the discharge voltage curve is a sloped (eg, gently and / or monotonically sloped) portion of the discharge voltage curve.
34. A cathode material comprising a mixture of: at least one electroactive sulfur material; and At least one non-sulfur electroactive material, the non-sulfur electroactive material being a mixed metal chalcogenide, wherein the at least one non-sulfur electroactive material has a discharge voltage curve corresponding to the discharge voltage curve of the at least one electroactive sulfur material.
35. The cathode material of claim 34, wherein the at least one non-sulfur electroactive material comprises two non-sulfur electroactive materials (two mixed metal chalcogenides).
36. The cathode material of claim 34, wherein the at least one non-sulfur electroactive material is a single non-sulfur electroactive material (single mixed metal chalcogenide).
37. The cathode material of any one of claims 34 to 36, wherein the mixed-metal chalcogenide is a mixed-metal sulfide (e.g., wherein the mixed-metal chalcogenide is a mixed-metal sulfide wherein the at least one non-sulfur electroactive material comprises two non-sulfur electroactive materials).
38. The cathode material of any one of claims 34 to 37, wherein the discharge voltage curve of the at least one non-sulfur electroactive material has a voltage plateau close to a voltage plateau of the at least one electroactive sulfur material.
39. The cathode material of any one of claims 34 to 38, wherein the at least one non-sulfur electroactive material has a discharge voltage curve characterized by a discharge voltage attributable to the at least one non-sulfur material being within 10% (e.g., within 5%, within 3%, or within 1%) of a sulfur discharge voltage attributable to the at least one electroactive sulfur material for at least 50% of the total discharge (e.g., for at least 60%, at least 75%, or at least 80% of the total discharge).
40. The cathode material of any one of claims 34 to 39, wherein the at least one electroactive sulfur material comprises at least one of the following (i) to (iv): (i) sulfur in the form of an S8 cyclic octaatomic molecule, (ii) sulfur in the form of a lithium sulfide (e.g., Li2S2 and / or Li2S), (iii) sulfur in the form of an electroactive organic sulfur compound, and (iv) sulfur in the form of an electroactive sulfur-containing polymer.
41. The cathode material of any one of claims 34 to 40, wherein the discharge voltage curve of the at least one non-sulfur electroactive material has two voltage plateaus, wherein one of the two plateaus corresponds to a soluble / intermediate polysulfide conversion and the other of the two plateaus corresponds to a solid or quasi-solid product.
42. The cathode material of any one of claims 34 to 41, wherein the discharge voltage curve of the at least one non-sulfur electroactive material has two voltage plateaus, wherein the first plateau is between about 2.2 and about 2.4 (V, relative to Li / Li + ) range, and the second platform is about 2.0 to about 2.2 (V, relative to Li / Li + ) range.
43. The cathode material of any one of claims 34 to 42, wherein the at least one non-sulfur electroactive material has a discharge voltage curve close to the discharge voltage curve of sulfur to lithium sulfide (e.g., S8→Li2S).
44. The cathode material of any one of claims 34 to 43, wherein the cathode material is at least 10 mass % non-sulfur electroactive material (e.g., a mixed metal chalcogenide) relative to sulfur (e.g., 10 to 90 mass % non-sulfur electroactive material, e.g., 30 to 70 mass % non-sulfur electroactive material).
45. A battery comprising (i) a cathode comprising the cathode material of any one of claims 34 to 44, and (ii) an electrolyte (eg, a solid state electrolyte (SSE)) in contact with the cathode.
46. The battery of claim 45, further comprising an anode.
47. The battery of claim 46, wherein the anode is a protected lithium metal anode.
48. The battery of claim 45, further comprising a protected current collector.
49. A cathode comprising the cathode material of any one of claims 1 to 19 and 34 to 44 (eg, and a binder and / or conductive carbon).
Citation Information
Patent Citations
3D self-assembled multi-modal carbon-based particles integrated into a continuous electrode film layer
US11299397B2
Electrochemical cell and method of making the same
US20160172660A1
Electrochemical cell and method of making the same
US20160172661A1
Encapsulated sulfur cathodes for rechargeable lithium batteries
WO2013040067A1
Core-shell structured nanoparticles for lithium-sulfur cells
WO2014074150A1